The Influence of Work Culture and Transformational Leadership Style on Employee Performance with Career Opportunities as a Mediating Variable at PT Mandiri Utama Finance, Cibubur Branch - Faisal Ritonga (Pustaka Digital Indonesia, 2025)
Work culture, Transformational Leadership Style , and Career Opportunities are factors which is thought to have a relatively large influence on the performance of PT employees Mandiri Utama Finance Cibubur branch . To find out the influence, a study was conducted This with objective analyze influence culture Work, style transformational leadership , and career opportunities on employee performance at PT Mandiri Utama Finance. Research This done in PT Independent Main Finance branch Cibubur by taking 100 employees as a research sample. Which is used using a quantitative approach. To test the hypothesis, multiple linear regression is used, as well as t-test and F-test. the results of the study are thought to indicate that employee performance can be influenced by work culture and transformational leadership style, and career opportunities are also a major consideration in maintaining the consistency of employee performance results.